Quasirelativistic two-component core excitations and polarisabilities from a damped-response formulation of the Bethe–Salpeter equation. (16th November 2020) - Kehry, Max; Franzke, Yannick J.; Holzer, Christof; Klopper, Wim
Abstract : A damped-response formalism in the GW approximation to the Bethe–Salpeter equation (BSE) is presented and implemented. It is based on a quasirelativistic two-component (2c) approach that includes scalar-relativistic and spin–orbit effects derived from the one-electron Dirac equation. A generalised solver, which also allows to calculate static, dynamic and damped-response polarisabilites, is discussed in detail. Throughout our implementation, the resolution-of-the-identity approximation is employed to reduce the computational effort. The performance of 2c GW -BSE is benchmarked against experimental and high-level ab initio data and compared to standard density-functional theory approaches, including modern local hybrid functionals for which a proper non-collinear kernel for Kramers-restricted systems is reported. GRAPHICAL ABSTRACT: